PELATIHAN MEDIA ENGLISH LANGUAGE CAFE GURU BAHASA INGGRIS MGMP MAN JOMBANG - Daristin, Pipit Ertika; Agustina, Ria Kamilah; Zuhriyah, Mukminatus; Fajarina, Maskhurin; Ma'rifatulloh, Sayid; Nurul Laili, Elisa (ABIDUMASY, 2024)
In an effort to implement the Independent Curriculum, English teachers face a major challenge in creating creative and innovative teaching materials. The Independent Curriculum gives teachers the freedom to determine teaching methods and teaching materials that suit students' needs, but this also requires high creativity from teachers (Kemendikbud, 2021). Many teachers are still trapped in conventional teaching patterns and find it difficult to develop interesting and interactive materials (Putri, 2023). In this training, a program was implemented in the form of training to increase knowledge and insight related to physical visual teaching materials. Therefore, the approach methods used are presentations, lectures, practice, questions and answers, discussions, simulations, and pair or group work. The results of this training are that English teachers at the MGMP MAN Kab Jombang level are able to create innovative and contemporary media teaching materials to increase students' learning motivation in class. Keywords: Independent Curriculum, Teaching Media, English Language Cafe